Adaptation to climate change: A study on regional urban water management and planning practice. (25th June 2022) - Ray Biswas, Rahul; Sharma, Raj; Gyasi-Agyei, Yeboah
Abstract: Advancing knowledge on how climate change impacts on water resources is considered a priority in the academic world. This paper studies the strategies adopted by urban water professionals in the tropical region of Queensland, Australia to minimise the impacts of climate change on the regional urban water supply network. In the recent past, the dry tropical urban region of Queensland has faced a climate-induced water crisis (2014–2018). This article investigates the urban water distribution authorities' planning and operational practices as part of climate change adaptation in the study region. Water professionals from the local urban water authorities were interviewed using a comprehensive range of questionnaires. Although the impacts of climate change on different water supply sources have been investigated in many parts of Queensland, the adaptation measures taken by the local authorities appear to be random and unplanned. Holistic implementation of climate change adaptation is rare and at its infancy stage due to the lack of quantifiable implementation frameworks or an audit process. The result shows resource constraints and lack of government support are the two major barriers to climate change adaptation in the water sector. Some water practitioners believe that the local urban water authorities have done a reasonable job on climate change adaptations in bits and pieces considering a wide range of local challenges such as lack of support from stakeholders, limited resources, and technology. Some other participants believe that too much attention on climate change will cause a noticeable problem in economic activities unless concerns from all stakeholders receive equal attention and are addressed. This is an important point and deserves proper acknowledgement to overcome relevant political and community barriers to climate change adaptation. The study concludes with a critical discussion on various strands of climate change adaptation to address the long-term regional urban water supply security challenges.